2021
DOI: 10.1002/hyp.14014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic variability in black ash wetlands: Implications for vulnerability to emerald ash borer

Abstract: Black ash (Fraxinus nigra) wetlands are widespread, forested landscape features in the western Great Lakes region. However, the future of these ecosystems is threatened due to impending spread of the invasive emerald ash borer (EAB), which results in tree mortality, decreased transpiration, and potential shifts to wetter, non-forested

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…The positive feedback loop that results sets up conditions under which a regime shift from forested riparian zone to a sedge/herbaceous dominated wetland can occur because of EAB‐induced ash mortality. This has been previously documented in black ash wetland systems (e.g., Cianciolo et al, 2021; Diamond et al, 2018) and is likely driving the riparian zone ecosystem responses observed in this and other recent studies (e.g., Engelken et al, 2020; Engelken & McCullough, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…The positive feedback loop that results sets up conditions under which a regime shift from forested riparian zone to a sedge/herbaceous dominated wetland can occur because of EAB‐induced ash mortality. This has been previously documented in black ash wetland systems (e.g., Cianciolo et al, 2021; Diamond et al, 2018) and is likely driving the riparian zone ecosystem responses observed in this and other recent studies (e.g., Engelken et al, 2020; Engelken & McCullough, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…The ground points can be extracted from the dense point cloud generated by terrestrial LiDAR to create a high-resolution DEM. Several researchers [2,25,27,32,92,93] used opensource CloudCompare software to extract ground points. The extraction of ground points requires a point cloud library (PCL, see [94]) to remove noise and outlier points.…”
Section: Microtopography Acquisition With Terrestrial Lidarmentioning
confidence: 99%
“…Invasive insects and pathogens reduce the essential services trees provide in multiple settings ranging from wilderness areas to urban communities (figure 1; Bradshaw et al 2016, Fei et al 2019. The negative acute and chronic environmental impacts of nonnative pests include reduced ecosystem services, such as carbon sequestration, biodiversity, genetic diversity, hydrology, soil functions, and energy conservation (box 1) (Gandhi and Herms 2010b, Boyd et al 2013, Freer-Smith and Webber 2017, Hauer et al 2020, Cianciolo et al 2021. The negative economic impacts include reduced abundance and quality of wood products, quarantine restrictions on market access, reduced residential property values, and the costs of managing established populations (Holmes et al 2009, Aukema et al 2011, Kenis et al 2017.…”
mentioning
confidence: 99%